Design of Vibration Absorber using Spring and Rubber for Armored Vehicle 5.56 mm Caliber Rifle - Nugraha, Aditya Sukma; Budiwantoro, Bagus; Rijanto, Estiko (Research Centre for Electrical Power and Mechatronics, Indonesian Istitutes of Sciences, 2014)
This paper presents a design of vibration absorber using spring and rubber for 5.56 mm caliber rifle armored vehicle. Such a rifle is used in a Remote-Controlled Weapon System (RCWS) or a turret where it is fixed using a two degree of freedom pan-tilt mechanism. A half car lumped mass dynamic model of armored vehicles was derived. Numerical simulation was conducted using fourth order Runge Kutta method. Various types of vibration absorbers using spring and rubber with different configurations are installed in the elevation element. Vibration effects on horizontal direction, vertical direction and angular deviation of the elevation element was investigated. Three modes of fire were applied i.e. single fire, semi-automatic fire and automatic fire. From simulation results, it was concluded that the parallel configuration of damping rubber type 3, which has stiffness of 980,356.04 (N/m2) and damping coefficient of 107.37 (N.s/m), and Carbon steel spring whose stiffness coefficient is 5.547 x 106 (N/m2) provides the best vibration absorption.Â